Pengaruh Pemberian Lactobacillus dengan Dosis Berbeda untuk Menekan Vibrio pada Air Budidaya Udang Vaname: (Litopenaeus Vannamei) - Tarisa Romadhani Farmawati; Indra Wirawan; Muhajir Muhajir (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Vibrio sp. is one of the main pathogenic bacteria causing various diseases in whiteleg shrimp (Litopenaeus vannamei) cultivation, such as vibriosis, which can reduce the survival rate and productivity of ponds. Environmentally friendly Vibrio control efforts can be achieved through the use of probiotics. One widely used probiotic is Lactobacillus sp., which is known to suppress the growth of pathogenic bacteria through competition for space and nutrients, production of antimicrobial compounds (bacteriocins and organic acids), and increased shrimp non-specific immunity. This study aimed to determine the effectiveness of administering different doses of Lactobacillus sp. in suppressing Vibrio sp. populations in whiteleg shrimp cultivation media. The method used was a Completely Randomized Design (CRD) with four treatments and five replications: control (A), 6 ppm lactobacillus sp (B), 12 ppm (C), and 18 ppm (D). The parameter observed was the Total Vibrio Count (TVC) in the culture water after 24 hours of lactobacillus administration.